2018
DOI: 10.1111/fcp.12350
|View full text |Cite
|
Sign up to set email alerts
|

The new therapeutic herbal drug HM0601 and its bioactive compound rutin exert potent antiproliferative activities in mast cells

Abstract: HM0601 consists of Allium hookeri and Lycium chinense fruit and contains a lot of rutin. Here, we ascertained whether HM0601 and its major compound rutin reduce proliferation of human mast cell line, HMC-1, under thymic stromal lymphopoietin (TSLP) stimulation. Therapeutic rutin or HM0601 treatment considerably reduced proliferation of mast cells without exposing activated HMC-1 cells to any cytotoxicity. Reduced levels of mouse double minute 2 and phosphorylated signal transducers and activators of transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…We have made a novel observation in this study that phytochemicals differentially modify cell surface expression of FcεRI and KIT in human and mouse MC. Quercetin causes a drastic reduction in FcεRI expression in BMMC ( Figure 3 ) and this correlates with a decrease in de novo cytokine (TNF) production ( Figure 4 D) which confirms earlier reports by Jeong et al and Krajewski et al [ 43 , 55 ]. The mechanism behind this change in cell surface expression of FcεRI is currently unknown.…”
Section: Discussionsupporting
confidence: 90%
“…We have made a novel observation in this study that phytochemicals differentially modify cell surface expression of FcεRI and KIT in human and mouse MC. Quercetin causes a drastic reduction in FcεRI expression in BMMC ( Figure 3 ) and this correlates with a decrease in de novo cytokine (TNF) production ( Figure 4 D) which confirms earlier reports by Jeong et al and Krajewski et al [ 43 , 55 ]. The mechanism behind this change in cell surface expression of FcεRI is currently unknown.…”
Section: Discussionsupporting
confidence: 90%
“…The higher activity of GPx and GR in Allium roseum compared to Allium sativum strengthens the antioxidant capacity of the Allium roseum bulbs. R is a flavonoid that is widely found in fruits and vegetables and the high levels observed bulbs, flowers bulblets and especially in flowers of Allium roseum make it a potential new sources for this bioactive compound with therapeutic and nutritive purposes [29]. Some studies investigate the possible uses of Allium flowers for their nutritional and health properties [30] [31].…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of AA, GSH, R and the elevated activity of GR and CAT were found in the garlic leaves, in comparison to the bulbs, and this provides new information for Allium sativum, particularly because the leaves are less used and investigated. Recently, interest in the wild Allium species has grown and these results provide new information for the Allium roseum, a wild-growing Allium species, which is less studied and the references to nutritional and medical applications are rarely given [29]…”
Section: Discussionmentioning
confidence: 99%
“…e fact that the total flavonoids level in L. chinense was higher than those of most vegetables, therefore indicating the greater health value of L. chinense [40,56,57]. Rutin and chlorogenic acid were the dominant flavonoids in L. chinense; they are important for the prevention of allergic inflammatory diseases and have antiinflammatory and antiangiogenic effects, as well as protective effects on the retinal ganglion; this suggests their great value in eye health and in prevention of cardiovascular and cerebrovascular diseases [55,58,59]. In our study, higher contents of rutin and chlorogenic acid were found in L. chinense than have been reported for L. barbarum; this is consistent with previous studies [43].…”
Section: Rutin Contentmentioning
confidence: 99%